The integral expression given is,
![\int (x+3)/(x^2+5x-6)dx](https://img.qammunity.org/2023/formulas/mathematics/college/2kmhez0b1snqr1c6svh714atkj5k4y41bg.png)
Neglecting the integral sign, and solve the the polynomial as a partial fraction
![(x+3)/(x^2+5x-6)](https://img.qammunity.org/2023/formulas/mathematics/college/mdr7bj258wvy2zpqh0lh3b13bpbxnj4kph.png)
Let us factorize the denominator
![\begin{gathered} x^2+5x-6 \\ (x^2-x)+(6x-6) \\ ^{}x(x-1)+6(x-1) \\ (x+6)(x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b2aetc3ig4w0zbydkogujbuwhts90ihi9v.png)
Therefore,
![(x+3)/(x^2+5x-6)=(x+3)/((x+6)(x-1))](https://img.qammunity.org/2023/formulas/mathematics/college/ltgkgupo5ei3y8grr81zz0xd8643yrx1vy.png)
Expanding the expression using partial fraction
![\begin{gathered} (x+3)/((x+6)(x-1))=(A)/(x+6)+(B)/(x-1) \\ (x+3)/((x+6)(x-1))=(A(x-1)+B(x+6))/((x+6)(x-1)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4lcbijinhqv5ztbl9iz1mwaabdg7ysqirz.png)
Multiply both sides by sides by (x+6)(x-1), we will have
![x+3=A(x-1)+B(x+6)](https://img.qammunity.org/2023/formulas/mathematics/college/kgeyd7o0h76ykl16sh87vh7pkb7mxhg5tx.png)
Substiute x = 1, into the equation above and solve for the value of B
![\begin{gathered} 1+3=A(1-1)+B(1+6) \\ 4=A(0)+7B_{_{}} \\ 4=_{_{_{}}}0+7B \\ 4=7B \\ (4)/(7)=(7B)/(7) \\ (4)/(7)=B \\ \Rightarrow B=(4)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pqp29vs13c361v986jgj0rcfjv9a46jlf8.png)
Substiute x = -6, into the equation above and solve for the value of A
![\begin{gathered} -6+3=A(-6-1)_{}+B(-6+6) \\ -3=A(-7)+B(0)=-7A+0 \\ -3=-7A \\ (-3)/(-7)=(-7A)/(-7) \\ (3)/(7)=A \\ \Rightarrow A=(3)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y8s49w44coxgytgu53pd1daxlqmx3d98bi.png)
Hence,
![\begin{gathered} (x+3)/((x+6)(x-1))=(3)/(7(x+6))+(4)/(7(x-1)) \\ (x+3)/((x+6)(x-1))=(1)/(7)\lbrack(3)/((x+6))+(4)/((x-1))\rbrack \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eogttd6vedh41fgl2p9os9wzv5kej4dnmo.png)
Now let us now install our answer back into the integral form
![\int (x+3)/(x^2+5x-6)dx=\int (1)/(7)\lbrack(3)/((x+6))+(4)/((x-1))\rbrack dx](https://img.qammunity.org/2023/formulas/mathematics/college/sxs42lw1x5uhs4js45dkswdmtrt4mj6etk.png)
Hence, the correct option is Option C.